2020
DOI: 10.3390/vaccines8040577
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Modified Live Chimeric Marker Vaccine against BVDV-1 and BVDV-2

Abstract: Bovine viral diarrhea virus (BVDV), a pestivirus which exists in the two distinct species BVDV-1 (syn. Pestivirus A) and BVDV-2 (syn. Pestivirus B), is the causative agent of one of the most widespread and economically important virus infections in cattle. For economic as well as for animal health reasons, an increasing number of national BVDV control programs were recently implemented. The main focus lies on the detection and removal of persistently infected cattle. The application of efficient marker or DIVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…The overall aim of this study was to develop a marker vaccine prototype for BVDV-1 using a novel approach based on a synthetic backbone strategy of a related pestivirus with chimeric protein expression that has successfully been employed previously [46]. The synthetic backbone strategy allows the rapid exchange, deletion or insertion of sequences or genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall aim of this study was to develop a marker vaccine prototype for BVDV-1 using a novel approach based on a synthetic backbone strategy of a related pestivirus with chimeric protein expression that has successfully been employed previously [46]. The synthetic backbone strategy allows the rapid exchange, deletion or insertion of sequences or genes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study characterizing a CSF mutant virus has already shown that the deletion of N pro and the absence of the immunosuppressive function led to an attenuation in vivo [54]. Despite that, most of the N pro encoding sequences were deleted in our construct in order to further increase the safety for pregnant dams, a concept already applied for the commercial BVDV vaccine Bovela ® (Boehringer Ingelheim Vetmedica GmbH, Ingelheim/Rhein, Germany) and the previously described marker vaccine candidates BVDV-1b_synCP7_∆N pro _E rns Bungo and BVDV-1b_synCP7_∆N pro _E rns Bungo_E1E2CS [46]. Regarding the factor of the heterologous heterodimer of E1 and E2 that might negatively influence the in vitro growth of BuPV_∆N pro _E1E2 CP7, we selected the combined replacement of both proteins because of the high genetic diversity between BuPV and BVDV-1 and as the formation of E1-E2 heterodimers is essential for virus entry [55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the significance of PI animals for spreading the infection, the target of vaccination strategies against BVDV mainly focuses on fetal protection, in addition to preventing clinical disease and virus-induced immune dysregulation. Control vaccination programs against BVDV involved using different types of live attenuated, killed, and recombinant vaccines (132)(133)(134)(135)(136). Although several scientific reports suggested their ability to prevent the clinical BVDV manifestations in cattle, live attenuated and killed BVDV vaccines differ in their safety for the vaccination of different cattle populations.…”
Section: Recent Advances On Bvdv Vaccination and Immunotherapeutic Strategiesmentioning
confidence: 99%